IMPLEMENTASI SOSTAC DALAM STRATEGI KOMUNIKASI MARKETING PUBLIC RELATIONS (STUDI DESKRIPTIF KUALITATIF PADA RUANG KREATIF GEDUNG DHARMA NEGARA ALAYA DENPASAR) - I.M. Bayu Mahardika; I Dewa Ayu Hendrawathy Putri; I Gusti Ngurah Pertu Agung (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The research was conducted to find out public relations marketing communications in the creative space of Dharma Negara Alaya Denpasar. In response to the program set by the city government of Denpasar in the form of the creative space of Dharma Negara Alaya’s building. The question examined from this study is: 1) How is the implementation of SOSTAC in public relations marketing communication strategy on the creative space of Dharma Negara Alaya Denpasar? 2) What is the public relations marketing strategy in the creative space of Dharma Negara Alaya Denpasar? 3) How are public relations marketing the creative space of the Dharma Negara Alaya Denpasar building? With descriptive qualitative research, analysis results with the SOSTAC method for digital marketing strategy and public relations marketing communication strategy. After being analyzed with the SOSTAC method, then each problem formulation is dissected with public relations theory, persuasive communication theory, and symbolic interactionism theory. The results of the study show that 1) SOSTAC (Situation, Objective, Strategy, Tactic, Action, Control) implementation is by the implementation of communication carried out by the public relations team, 2) Communication strategies are carried out in a persuasive and educative manner to attract public interest, 3) Dharma Negara Alaya has a high commitment to the implementation of public service standards that have been set. In conclusion, the implementation of marketing public relations communications is following the principles and hierarchy of the organization, carrying out public communications properly, professionally, and under procedures as the researchers have concluded. Keywords: SOSTAC, Public Relations, Public Communication, Marketing